Petrology and Provenance of Lithic Raw Materials used to knap stone: A Case Study From the Inner Ionian Sea - Magganas, Andreas; Galanidou, Nena; Chatzimpaloglou, Petros; Kati, Marianna; Iliopoulos, Giorgos; Katerinopoulos, Athanassios (Bulletin of the Geological Society of Greece, 2019)
This paper examines the lithology and raw material provenance of knapped stone artifacts recovered from prehistoric sites on Meganisi in the course of the Inner Ionian Sea Archipelago survey. Research was twofold: in the field to map the geology of the island and collect raw material samples, and in the laboratory to conduct a petrological study using LM, XRD, SEM and ICP-MS techniques. The greater part of the materials used to produce stone tools consists of almost pure SiO2, bedded or nodular cherts mainly of Malm–Turonian and Eocene ages. The cherts were collected by prehistoric knappers from local sources. Patinas present on the artifacts are relatively enriched in calcite material of incomplete silica diagenesis and subsequently a product of late weathering and alteration.